FAKTOR EKONOMI YANG MEMENGARUHI INDEKS HARGA SAHAM DI BURSA EFEK INDONESIA (BEI) PERIODE 2010-2014 - Dr. Said kelana (Jurnal Manajemen, 2016)
Macroeconomic factors can affect stock price indexes, both Sectoral Index and Composite Index. These factors include exchange rate of Rp / US $, T-bill rate, and inflation. These factors affect the performance of company (issuer) in the real market, and further on the performance of the stock market. This study uses data from 2010-2014. Regression result shows T-bill rate variable has negative effect to share price index.Â Key Words: Common Factors, Composite Index, Exchange Rate, T Bill Rate; InflationÂ